PENGEMBANGAN BOOKLET KEANEKARAGAMAN GASTROPODA DI PANTAI CUKUH RAYA KABUPATEN KAUR SEBAGAI BAHAN AJAR KLASIFIKASI MAKHLUK HIDUP UNTUK SISWA SMP - Agustina, Resta; Johan, Henny; Primairyani, Ariefa; Nursa’adah, Euis; Wikrama Wardana, Rendy (Jurnal Biogenerasi, 2024)
The purpose of this study was to determine the diversity of gastropods on Cukuh Raya Beach, Kaur Regency and to produce a valid classification booklet of living things. Based on the results of sampling at Cukuh Raya Beach, 12 species of gastropods were obtained, namely: M. annulus, T. chrysostomus, T. canaliculatus, R. aspera, N. canrena, C. femorale, V. musica, N. undata, T. radiatus G., R. nilotica, O. sayana R., and O. polpasta D. The research and development design used, namely (R&D) is based on the 4-D model starting from defining (Define), designing (Design), developing (Develop), and disseminating (Disseminate), but only carried out up to the development stage. The booklet developed was made with an attractive cover and Open Sans font that is in accordance with EYD. The booklet contains a front cover, foreword, table of contents, learning objectives, indicators of learning objective achievement, summary of materials, gastropod diversity, evaluation questions, and bibliography. The average results by expert (lecturer) and practitioner (teacher) validation obtained a percentage of the booklet content aspect of 90%, language aspect of 93.8%, and graphic/design aspect of 88.6% with an average of 90.8% in the category of "very feasible". Thus, it can be concluded that the developed product is very feasible to be tested in the learning process.